Media Framing of Gibran Rakabuming’s 2024 Candidacy Post-Constitutional Court Ruling - Fitriatun; Edi Nurwahyu Julianto (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze how online media Kompas.com frames dynastic political issues, especially those involving President Joko Widodo's family, namely Gibran Rakabuming Raka and Kaesang Pangarep. Theoretical framework: The theoretical framework used in this study is a framing model from Robert Entman, which consists of four elements: defining problems, diagnosing causes, making moral judgments, and suggesting solutions. Literature review: The literature review in this study includes a study of framing theory in media studies, the dynamics of dynastic politics in Indonesia, and the role of media in contemporary democracy. Methods: The method used was an analysis of the framing of the Entman model of some Kompas.com news that discussed dynastic political issues, focusing on content related to the President's family. Results: The results of the study show that Kompas.com framing dynastic politics as a significant issue in Indonesian democracy with a relatively balanced approach, presenting a critique of the potential for nepotism, but also presenting the argument that political decisions remain in the hands of the people. Implications: These findings imply that the media has an important role in shaping public discourse related to dynastic politics, as well as being able to balance criticism and neutrality in conveying politically sensitive issues. Novelty: The novelty of this study lies in its focus on the way Indonesia's mainstream media frames dynastic politics in the context of the presidential family, as well as the systematic application of Entman's framing model to understand the media's construction of the issue in the Indonesian democratic landscape.